Kidney disorders after Hymenoptera stinging. - Tangvoraphonkchai, K. (Chulalongkorn Medical Journal, 2023)
Hymenptera sting still exists in rural areas of Thailand. Most patients present with skin lesions that almost physicians can manage, sometimes they may present with anaphylaxis or severe complications leading to morbidity and mortality. Acute kidney injury and other kidney disorders such as acute cortical necrosis, nephrotic syndrome and renal tubular acidosis are rare manifestations. These always impact survival and clinical outcomes and every physicians should realize and promptly manage before renal replacement therapy is need. This article discusses Hymenoptera sting induced kidney disorders and up-to-date management.